2019
DOI: 10.1002/biof.1550
|View full text |Cite
|
Sign up to set email alerts
|

A review of the pharmacological and therapeutic effects of auraptene

Abstract: There is a growing awareness in herbal medications as they are usually safe and devoid of significant adverse effects. Auraptene is a natural bioactive monoterpene coumarin ether and is consumed all over the world. There is growing evidence of the therapeutic benefits of auraptene. Auraptene, also known as auraptene and 7‐geranyloxycoumarin, is a bioactive monoterpene coumarin from Rutaceae family, which is isolated from Citrus aurantium (Seville orange) and Aegle marmelos (bael fruit). Auraptene is a highly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 56 publications
(116 reference statements)
0
24
0
Order By: Relevance
“…For example, auraptene, a citrus coumarin endowed with anti-inflammatory properties [299], acts as neuroprotective agent in the 2VO mouse model of brain ischemia by inhibiting inflammation [300,301].…”
Section: Coumarinsmentioning
confidence: 99%
“…For example, auraptene, a citrus coumarin endowed with anti-inflammatory properties [299], acts as neuroprotective agent in the 2VO mouse model of brain ischemia by inhibiting inflammation [300,301].…”
Section: Coumarinsmentioning
confidence: 99%
“…The only biochemical parameters recorded were common blood exam values, mostly expressing liver functionality, that in the treated group of volunteers interestingly were not significantly different from values recorded in the control one. To this context it is noteworthy how the only two studies reported in the literature about pharmacokinetic of auraptene are still represented by those obtained in animal models, namely dogs and rats, and published respectively by Yuan et al (2012) and Ye et al 2016, the details of which can be found in previously published review articles on auraptene (Bibak et al 2019;Genovese et al 2015). So, it is desirable that in the next future the pharmacokinetic profile of auraptene in humans could be traced to largely contribute to the determination to its safety for humans.…”
Section: Auraptenementioning
confidence: 99%
“…Auraptene is isolated from many of the edible fruits and vegetables of the genus Ferula and Citrus like lemons, grapefruits and oranges. Auraptene indicates a variety of therapeutic properties such as antidiabetic, antiprotozoal, anti-bacterial, anti-fungal, anti-genotoxic, antileishmanial, anti-inflammatory, antihelicobacter, and immunomodulatory activities ( Bibak et al, 2019 ). This compound showed significant effect on the treatment of several chronic illnesses including hypertension, nonalcoholic fatty liver and cystic fibrosis ( Derosa et al, 2016 ; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%